Curcumin suppresses oncogenicity of human colon cancer cells by covalently modifying the cysteine 67 residue of SIRT1. (1st September 2018) - Lee, Yeon-Hwa; Song, Na-Young; Suh, Jinyoung; Kim, Do-Hee; Kim, Wonki; Ann, Jihyae; Lee, Jeewoo; Baek, Jeong-Heum; Na, Hye-Kyung; Surh, Young-Joon
Abstract: SIRT1, an NAD + -dependent histone/protein deacetylase, has diverse physiological actions. Recent studies have demonstrated that SIRT1 is overexpressed in colorectal cancer, suggesting its oncogenic potential. However, the molecular mechanisms by which overexpressed SIRT1 induces the progression of colorectal cancer and its inhibition remain largely unknown. Curcumin (diferuloymethane), a major component of the spice turmeric derived from the plant Curcuma longa L., has been reported to exert chemopreventive and anti-carcinogenic effects on colon carcinogenesis. In the present study, we found that curcumin reduced the expression of SIRT1 protein without influencing its mRNA expression in human colon cancer cells, suggesting posttranslational regulation of SIRT1 by this phytochemical. Notably, ubiquitination and subsequent proteasomal degradation of SIRT1 were induced by curcumin treatment. Results of nano-LC-ESI-MS/MS revealed the direct binding of curcumin to cysteine 67 of SIRT1. In line with this result, the protein stability and clonogenicity of a mutant SIRT1 in which cysteine 67 was substituted by alanine were unaffected by curcumin. Taken together, these observations suggest that curcumin facilitates the proteasomal degradation of oncogenic SIRT1 through covalent modification of SIRT1 at the cysteine 67 residue. Highlights: SIRT1 is overexpressed in colorectal cancer tissues compared with normal colon tissues. SIRT1 knockdown attenuates viability and migration of human colon cancer cells. Silencing of SIRT1 suppressed the growth of HCT-116 derived tumor xenografts. Curcumin inhibits migration and growth of HCT-116 cells. Curcumin covalently modifies SIRT1 on the cysteine 67 residue, thereby stimulating its proteasomal degradation.